Ocular and Plasma Pharmacokinetics of Sitagliptin Eye Drops: Preclinical Data - Cristina Hernández; Hugo Ramos; Anne Létondor; Rafael Simó (Pharmaceuticals)
Background/Objectives: Early stages of diabetic retinopathy are currently considered an unmet medical need due to the lack of effective treatments beyond proper monitoring and control of glycemia and blood pressure. Sitagliptin eye drops have emerged as a new therapeutic approach against early stages of the disease, as they can prevent its main hallmarks, including both neurodegeneration and microvascular impairment. Interestingly, all of these effects occur without any glycemic systemic improvement. In the present study, we aimed to investigate the pharmacokinetics and distribution of the drug within the eye and plasma. Methods: A total of 48 male New Zealand rabbits were treated with topical administration (eye drops) of sitagliptin at two concentrations: 5 mg/mL and 10 mg/mL. Blood, iris/ciliary body, retina/choroid, aqueous humor, and vitreous humor samples were collected at specific intervals post-administration (10 and 30 min and 1, 3, 6, 15, and 24 h), processed, and analyzed using an LC-MS/MS method. The pharmacokinetics of sitagliptin were then calculated, and statistical comparisons were performed. Results: Our findings indicate that sitagliptin reaches the retina prior to the aqueous and vitreous humors, suggesting that its absorption follows the transscleral route. Additionally, systemic absorption was minimal and below pharmacologically active concentrations. Conclusions: These results support the use of an eye drop formulation for the treatment of diabetic retinopathy and other retinal diseases.